2021
DOI: 10.3389/fendo.2021.627210
|View full text |Cite
|
Sign up to set email alerts
|

Controversies on Endocrine and Reproductive Effects of Glyphosate and Glyphosate-Based Herbicides: A Mini-Review

Abstract: Glyphosate-based herbicides (GBHs) are among the most used pesticides worldwide, presenting high potential for human exposure. Recently, a debate was raised on glyphosate risks to human health due to conflicting views over its potential carcinogenic and endocrine disruptive properties. Results from regulatory guideline studies, reports from Regulatory Agencies, and some literature studies point to a lack of endocrine disrupting properties of the active ingredient glyphosate. On the other hand, many in vivo and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 60 publications
(68 reference statements)
0
23
0
1
Order By: Relevance
“…Likewise, other studies have shown that exposure to GBH promotes a reduction in the activity of enzymes responsible for metabolizing cholesterol and forming steroid hormones in the testis of the animals (Pham et al, 2019; Romano et al, 2010). Likewise, in females, a reduction in the activity of aromatase is found, which converts testosterone into estradiol, promoting an increase in this adipose panicle (De Araujo‐Ramos et al, 2021; Ingaramo et al, 2020). In line with these studies, we found an increase in the adipose tissue in danger, the main supplier of cholesterol for the production of these hormones.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, other studies have shown that exposure to GBH promotes a reduction in the activity of enzymes responsible for metabolizing cholesterol and forming steroid hormones in the testis of the animals (Pham et al, 2019; Romano et al, 2010). Likewise, in females, a reduction in the activity of aromatase is found, which converts testosterone into estradiol, promoting an increase in this adipose panicle (De Araujo‐Ramos et al, 2021; Ingaramo et al, 2020). In line with these studies, we found an increase in the adipose tissue in danger, the main supplier of cholesterol for the production of these hormones.…”
Section: Discussionmentioning
confidence: 99%
“…Certain groups of pesticides have the ability to modify the balance and function of the endocrine, immune, and neurological system (Cremonese et al, 2012;Pinheiro and Souza, 2017;de Araújo-Ramos et al, 2021). Therefore, fetal susceptibility to environmental exposure is even more critical if contact with these substances occurs early in the prenatal period, with risk of prematurity, low birth weight, reduced weight for gestational age, intrauterine growth retardation, reduced height and head circumference of the neonate, fetal death, poor Apgar score, and congenital malformations (CM), such as cryptorchidism and hypospadias (Cremonese et al, 2012;Carmichael et al, 2016;Froes Asmus et al, 2017;Ling et al, 2018;Toichuev et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Usually, formulants have more deleterious effects than glyphosate alone because of possible cumulative effects on endocrine and reproductive endpoints [106]. As summarized in Table 1, in female reproduction, glyphosate and GBHs exposure has consequences for post-natal ovarian and uterine development, puberty onset, oocyte maturation, sperm-oocyte binding ability and early embryo development, implantation and successful pregnancy.…”
Section: Gbhs In Roundup Formulationsmentioning
confidence: 99%